Differential regulation of proteasome functionality in reproductive vs. somatic tissues of Drosophila during aging or oxidative stress - Tsakiri, Eleni N. (Federation of American Societies for Experimental Biology, 2013)
Proteasome is central to proteostasis maintenance, as it degrades both normal and damaged proteins. Herein, we undertook a detailed analysis of proteasome regulation in the in vivo setting of Drosophila melanogaster. We report that a major hallmark of somatic tissues of aging flies is the gradual accumulation of ubiquitinated and carbonylated proteins; these effects correlated with a ∼50% reduction of proteasome expression and catalytic activities. In contrast, gonads of aging flies were relatively free of proteome oxidative damage and maintained substantial proteasome expression levels and highly active proteasomes. Moreover, gonads of young flies were found to possess more abundant and more active proteasomes than somatic tissues. Exposure of flies to oxidants induced higher proteasome activities specifically in the gonads, which were, independently of age, more resistant than soma to oxidative challenge and, as analyses in reporter transgenic flies showed, retained functional antioxidant responses. Finally, inducible Nrf2 activation in transgenic flies promoted youthful proteasome expression levels in the aged soma, suggesting that age-dependent Nrf2 dysfunction is causative of decreasing somatic proteasome expression during aging. The higher investment in proteostasis maintenance in the gonads plausibly facilitates proteome stability across generations; it also provides evidence in support of the trade-off theories of aging.—Tsakiri, E. N., Sykiotis, G. P., Papassideri, I. S., Gorgoulis, V. G., Bohmann, D., Trougakos, I. P. Differential regulation of proteasome functionality in reproductive vs. somatic tissues of Drosophila during aging or oxidative stress.